Evaluación Presupuestaria al Gobierno Autónomo Descentralizado de la Parroquia el Paraíso de Celén del Cantón Saraguro de la Provincia de Loja, Período 2013-2014”. - Macas Macas, Janeth del Carmen (2016)
The thesis "Budgetary Assessments Decentralized Autonomous Government to Parish the Paradise Çelen Canton Saraguro of the Province of Loja, 2013-2014 Period" has revealed compliance with institutional goals and objectives, she was conducted to to determine the degree of implementation of the budget and give a contribution to a company so that those responsible for managing the budget enabling them to ascertain the degree of compliance with the planned objectives in each period analyzed. To develop this research has been necessary to implement a methodology that is based on the technical standards Budget Code of Planning and Public Finance, etc. COOTAD the same to be applied mandatorily in the state. It has also compiled bibliographic material has been of great validity to understand regarding the budget cycle notably related to the evaluation, an interview was conducted after the President and the Secretary-Treasurer in order to determine the importance of the subject of study and know the main shortcomings of the entity. Then we proceeded to obtain supporting documentation such as: Bonds Income and Expenditure Budget, reports on budget implementation and annual operating plan of the institution which allowed determine the 5 degree of implementation of programs and activities planned by the institution. Financial Indices Budgetary Income Budgetary indices, indices of Budgetary Expenditures Budget Analysis reforms, in order to measure the degree of institutional management: Also the following indicators were applied. It concludes with a report which was prepared with the results due to the budget evaluation which is submitted for consideration to the highest authority, so that in the back can make better decisions and implementation in practice of the mission and vision which it was created entity. In general it can be concluded that the Autonomous Government Decentralized Parish Paradise Celen not properly planned budget which generates the failure to meet targets, so you are advised to refer historical data from previous years for a best estimate of the resources to be used and that these meet the needs of the parish.